Molecular determinants of sulfadoxine-pyrimethamine resistance in Plasmodium falciparum in Nigeria and the regional emergence of dhps 431V. Issue 3 (December 2016) - Oguike, Mary C.; Falade, Catherine O.; Shu, Elvis; Enato, Izehiuwa G.; Watila, Ismaila; Baba, Ebenezer S.; Bruce, Jane; Webster, Jayne; Hamade, Prudence; Meek, Sylvia; Chandramohan, Daniel; Sutherland, Colin J.; et al.
Abstract: There are few published reports of mutations in dihydropteroate synthetase ( dhps) and dihydrofolate reductase ( dhfr) genes in P. falciparum populations in Nigeria, but one previous study has recorded a novel dhps mutation at codon 431 among infections imported to the United Kingdom from Nigeria. To assess how widespread this mutation is among parasites in different parts of the country and consequently fill the gap in sulfadoxine-pyrimethamine (SP) resistance data in Nigeria, we retrospectively analysed 1000 filter paper blood spots collected in surveys of pregnant women and children with uncomplicated falciparum malaria between 2003 and 2015 from four sites in the south and north. Genomic DNA was extracted from filter paper blood spots and placental impressions. Point mutations at codons 16, 50, 51, 59, 108, 140 and 164 of the dhfr gene and codons 431, 436, 437, 540, 581 and 613 of the dhps gene were evaluated by nested PCR amplification followed by direct sequencing. The distribution of the dhps -431V mutation was widespread throughout Nigeria with the highest prevalence in Enugu (46%). In Ibadan where we had sequential sampling, its prevalence increased from 0% to 6.5% between 2003 and 2008. Although there were various combinations of dhps mutations with 431V, the combination 431V + 436A + 437G+581G+613S was the most common. All these observations support the view that dhps -431V is on the increase. In addition, P. falciparum DHPS crystal structure modelling shows that the change from Isoleucine to Valine ( dhps -431V) could alter the effects of both S436A/F and A437G, which closely follow the 2nd β-strand. Consequently, it is now a research priority to assess the implications of dhps- VAGKGS mutant haplotype on continuing use of SP in seasonal malaria chemoprevention (SMC) and intermittent preventive treatment in pregnancy (IPTp). Our data also provides surveillance data for SP resistance markers in Nigeria between 2003 and 2015. Graphical abstract: Highlights: We present data on dhps and dhfr mutations in P. falciparum populations in Nigeria. Increased prevalence of I431V mutation was seen between 2003 and 2015 from 0 to 36%. The 431V + 436A + 437G + 581G + 613S was the most common with dhps -431V mutation. Crystal structure modelling of Pf DHPS shows that 431Vcould alter S436A and A437G.